Management of hot tooth: Clinical challenges and emerging strategies: A narrative review - Prachod Krishnan (Bioinformation, 2026)
Symptomatic irreversible pulpitis (hot tooth) is a common endodontic problem characterized by severe spontaneous pain and difficulty in achieving profound local anesthesia. Accurate diagnosis and effective pain control remain major clinical challenges because intense pulpal inflammation lowers the pain threshold and increases nociceptive activity. These inflammatory changes reduce the success of conventional anesthetic techniques and may compromise endodontic treatment outcomes. Adjunctive approaches including supplemental anesthetic techniques, preoperative inflammation control and anxiety management can enhance anesthetic efficacy and patient comfort. Thus, data shows that integrating the mechanisms underlying anesthetic failure in hot teeth with evidence-based strategies for improving pain management and treatment success.